2000
DOI: 10.12968/denu.2000.27.8.384
|View full text |Cite
|
Sign up to set email alerts
|

It Ain't What You Say …: Legibility and Clarity of Treatment Records

Abstract: The content of treatment records is irrelevant if it cannot be understood. This is a report of a clinical audit project that aimed to assess the readability of records, and set standards to be maintained throughout the practice for handwriting and use of abbreviations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A study of the legibility of entries in over 900 handwritten dental records within a ninedentist practice in USA found that many records contained 'brief illegible graffiti which even the writer has trouble in deciphering at a subsequent visit'. 15 There was no uniformity in use of abbreviations within the practice.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the legibility of entries in over 900 handwritten dental records within a ninedentist practice in USA found that many records contained 'brief illegible graffiti which even the writer has trouble in deciphering at a subsequent visit'. 15 There was no uniformity in use of abbreviations within the practice.…”
Section: Discussionmentioning
confidence: 99%
“…Handwritten records have continuously been proven to be ineffective at capturing all the information required of them by assessors (2, 3, 7). Persian and Beckett (3) found even after a repeat audit, patient’s medical histories were not being checked at each visit; at best, the sample group achieved an 85% compliance rate.…”
Section: Discussionmentioning
confidence: 99%
“…Persian and Beckett (3) found even after a repeat audit, patient’s medical histories were not being checked at each visit; at best, the sample group achieved an 85% compliance rate. Smith and Farrington (7) carried out two audits of nine dentists, auditing dental record legibility. The range of legible records found by the first audit was between 24.2% and 100% with the second audit finding a range of 53% to 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The moment a clinician feels unable to express himself/herself on the CD and reaches for a pen, the CD is doomed. A print out must be available to place the patients’ records, preventing the clinician having to duplicate their records and the consequential failure of the project. The advantage of using a keyboard to input the data is the ability to read it. It has been shown (11) that despite meetings and audits seven out of the nine dentists’ handwriting fell below the agreed standard. For patients seen in the dental hospital by multiple dentists, the clinical records need to be a clear summary of what was seen and done, as opposed to ‘a brief illegible graffiti which even the writer has trouble in deciphering at the subsequent visit’ (11).…”
mentioning
confidence: 99%